PENGARUH KETAATAN ATURAN AKADEMIK MELALUI TINGKAT KEPUASAN MAHASISWA TERHADAP KEUNGGULAN BERSAING PERGURUAN TINGGI SWASTA DI KOTA MAKASSAR - Gempita, Gempita; Hatma, Ramli (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
Competition among private universities in Makassar City is intensifying with the development of globalization and technological advances. This situation requires each university to focus not only on improving service quality but also on ensuring adherence to academic regulations as a key pillar of quality educational governance. This study aims to analyze the effect of adherence to academic regulations on student satisfaction and competitive advantage at private universities in Makassar City, both directly and through the mediating variable of student satisfaction. The study used a quantitative approach using the Structural Equation Modeling (SEM) method with 265 student respondents from 10 private universities in Makassar City. The results show that adherence to academic regulations has a positive and significant effect on student satisfaction, and both directly and indirectly through student satisfaction, significantly influences the competitive advantage of universities. This demonstrates that good academic discipline can create student satisfaction and loyalty, ultimately strengthening the competitive position of universities in the era of globalization.